Agile design of public hospitals in Iran - Ghahraman Mahmoudi (Bali Medical Journal, 2018)
Background:Hospitals that are part of the organization because of the sensitivity and importance of the treatment must have in today's dynamic agile structure to be able to adapt to environmental changes. Therefore this study was to provide a structural model of agility in hospitals.Methods:This descriptive study was conducted in the year 2015. A total of 260 people were selected as sample from mentioned the statistical population. Validityof the questionnaire through examination exploratory and confirmatory factor analysis and reliability tests with Cronbach's alpha was approved 0.97. Data software 18 SPSS and 8.5 Lisrel a factor analysis using mathematical models the final model was developed based on confirmatory factor analysis confirmed the pattern was evaluated.Results:Question related to four agility (responsiveness, competence, flexibility, speed) are measured at the agility hospital And supply chain (independent variables) to correctly cover the variable and valid. Agile supply chain variable between maximum sensitivity and responsiveness(1.98±0.66) To develop the skills of employees received the lowest average (1.34±0.46) As well as structural equation modeling and all relationships were verified  (P-value < 0.001).Conclusions:Therefore, it is suggested to apply that to be successful and better adapted to the environment and achieve enhanced service quality, employee satisfaction and patients, competitiveness, reduce costs, reduce time to service delivery and organizational agility.